Analisis peningkatan nilai tambah agroindustri gula semut kelapa dengan diversifikasi produk - Hety Handayani Hidayat; Siswantoro; Rahman Fahrul Romadhoni (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: Coconut palm sugar is a commercial product that continues to experience a trend of progress in both local and global markets. This triggers competition between manufacturers. Therefore, it is necessary to make an effort to diversify products to be able to increase competitiveness. However, this diversification will certainly incur costs, so it is necessary to conduct studies aimed at increasing the added value of coconut palm sugar products with and without iodine fortification and statistically different testing of them. Methods: Value added analysis was conducted using the Hayami method. The increase between coconut palm sugar products and their diversification is calculated from the difference in value add. Then the two groups of products were tested for significant differences with Mann Whitney. Results: from the results of the study it was found that the value add increasing in coconut palm sugar with iodine fortification products was 7% or Rp. 2,086 per kg. In addition, from the results of the Mann Whitney test, it is statistically proven that the value add of the two products is significantly different, where the smallest U value is smaller than the calculated Z value (-1 28.58). Conclusion: Value add and profit can be increased by diversifying coconut palm sugar products into iodine fortified palm sugar.